Probability and Stochastic Processes with Applications to Communications, Systems and Networks, 2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Probability theory and stochastic processes are fundamental mathematical tools that play a critical role in understanding and modeling randomness and uncertainty in various fields, including communications, systems engineering, and network design. These concepts provide the foundation for analyzing and designing systems that operate in unpredictable environments, such as wireless communication networks, internet traffic, and signal processing systems. The current reprint is the continuation of the 1st Edition, representing a reprint of the second edition of the Special Issue “Probability and Stochastic Processes with Applications to Communications, Systems and Networks, 2nd Edition”. The collection covers a wide range of advanced topics in communication systems, queueing theory, stochastic processes, and optimization, with applications ranging from wireless networks to power grids and nanotechnology. It is our hope that it serves as a starting point for exploring the rich and fascinating world of probability and stochastic processes.